Neuroimaging Markers of Chronic Eye Diseases and Their Application Values - Yu, Chen-Yu; Huang, Rong; Li, Shi-Qi; Shao, Yi (Frontiers in Neurology, 2022)
In recent years, the impact of various chronic eye diseases on quality of life has become increasingly apparent. Therefore, it is particularly important to control the progress of chronic diseases at an early stage. Many studies have used neuroimaging methods to explore the effects of chronic eye diseases on the brain, and to identify changes in brain function that may act as markers for early diagnosis and treatment. This article reviews the clinical application of different techniques of functional magnetic resonance imaging in chronic eye diseases.